Hydrothermally growth of TiO2 Nanorods, characterization and annealing temperature effect - Falih M, Nada; Azara Hussain, Saleem; Khalaf Muhammad, Shawki; Alkhayatt, Adel H. Omran (Kuwait Journal of Science, 2021)
Titanium dioxide TiO2 nanorods were successfully grown on conductive glass FTO substrate by hydrothermal method at temperature 160 oC. Surface topography, structure and optical characteristics were studied according to the influence of annealing temperature (450, 550 and 650) oC. The surface topography results reveal that the TiO2 had nanorods structure with tetragonal shape and the rod diameter increases from 84.2 nm to 116.6 nm with increasing the annealing temperature. The crystal structure of the grown TiO2 NRs exhibits high crystallinity of polycrystalline nature with anatase and rutile phases. The preferential orientation was along (204) plane for anatase tetragonal structure. AFM image shows an intense edge, uniform surface morphology, and the grain diameter was increased with annealing temperature. The optical properties of TiO2 NRs were investigated and the absorption edge shows blue shifting as the annealing temperature increases when considering the crystallinity and morphology changes. The energy band gap was lower than 3 eV that can be attributed to the presence of anatase and rutile phases and increment from 2.72 to 2.86 nm with the increment of annealing temperature. The results indicate that the adopted hydrothermal method and the synthesized TiO2 NRs were suitable for photovoltaic and photocatalytic applications.